On the prevalence of framing effects across subject-pools in a two-person cooperation game - Sebastian J. Goerg; Gari Walkowitz (Max Planck Institute for Research on Collective Goods, 2010)
In this experimental study, involving subjects from Abu-Dis (West Bank), Chengdu (China), Helsinki (Finland), and Jerusalem (Israel), we test for a presentation bias in a two-person cooperation game. In the positive frame of the game, a transfer creates a positive externality for the opposite player, and in the negative frame, a negative one. Subjects in Abu-Dis and Chengdu show a substantially higher cooperation level in the positive externality treatment. In Helsinki and Jerusalem, no framing effect is observed. These findings are also reflected in associated first-order beliefs. We argue that comparisons across subject-pools might lead to only partially meaningful and opposed conclusions if only one treatment condition is evaluated. We therefore suggest a complementary application and consideration of different presentations of identical decision problems within (cross-cultural) research on subject-pool differences.
Keywords: A13; C72; C91; F51; Z13; 330; framing of decision problems; methodology; subject-pool differences; Framing; Entscheidung; Kooperatives Spiel; Test; Multikulturelle Gesellschaft; Vergleich; Westjordanland; China; Helsinki; Jerusalem